ANIMISM AND DYNAMISM BELIEF IN MUSLIM SOCIETY OF EAST NUSA TENGGARA - Kaltsum, Lilik Ummi (Jurnal Masyarakat dan Budaya, 2023)
This article is the result of research on animist beliefs and dynamism in the Muslim community of East Nusa Tenggara. This research begins with the phenomenon of the life of the local Muslim community who until now still believe in and undergo certain rituals. The variety of beliefs and rituals are an ancestral heritage that still relies on and favors spirits and also does something that is forbidden by Islam in order to obtain peace and safety. Therefore, this study is a field study that exploits the ethnographic method. This method is used by James Phillip Spradley as a science that explores culture and intends to find out other ways of life from the point of view of the people themselves. More precisely, this study tries to trace elements of belief, from religious rituals to events of death as well as beliefs that are still maintained. More precisely, the nuances of this exploratory research use a qualitative approach. The results of the study found that the form of belief in the Muslim community of East Nusa Tenggara, among others, is that people who die are believed to be dangerous for those who are still alive. If the residents can not maintain and respect it. If you want to build a house, you have to clean and or build graves around the land where the house will be built. If they do not do so, then the spirits will give trials that are detrimental to the owner of the house. This is the main problem of this research, normatively Islam requires its adherents to unite Allah in all their actions, not to pollute their beliefs with other beliefs or beliefs.